(untitled) (Conferencea, 2024)
This article discusses the analysis of the creative works of Isajon Sultan and Shukur Kholmirzayev. Also, there are opinions about the main idea of Isajon Sultan’s works, the scope of the subject and the events and characteristic features similar to the works of Shukur Kholmirzayev. There are views that Shukur Kholmirzayev’s and Isajon Sultan’s artistic skills in storytelling are related to the connection between nature and human life in the form of Isajon Sultan’s works. From the artist’s style of creating a work and the skill of using words, the image of nature takes on a wide range of roles.